(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The intricate relationship between dietary habits and sleep quality represents a multifaceted interplay that significantly influences overall health. This literature review synthesizes findings from various studies spanning different age groups and populations to provide a comprehensive understanding of this dynamic interaction. Adolescents’ experiences with sleep difficulties, prevalence of sleep disturbances in Chinese adolescents, and trends in self-reported sleep problems among Finish adolescents contribute to insights into the unique challenges faced by younger populations. Studies exploring short- and long-term health consequences of sleep disruption underscore the pervasive impact of disturbed sleep on well-being. Beyond adolescence, investigations into the correlation between lifestyle behaviors during pregnancy and postpartum depression, dietary patterns in medical students, and dietary intake among adults offer a broader perspective on the diverse factors influencing sleep quality. The review extends to include a comprehensive examination of interventions, challenges, and potential applications in promoting optimal sleep and nutritional well-being. Challenges, such as methodological heterogeneity and difficulty isolating specific factors, are discussed alongside the advantages and disadvantages of current research approaches.